Sobre una mutación del color del ojo en Rhodnius prolixus Stal, 1852, (Hemiptera, Reduviidae) - Rosabal, R.; Trejos, A. (Revista de Biología Tropical, 1966)
This report describes the finding of a red-eyed mutant of Rhodnius prolixus. Crossings show that the mutation is recessive. There is no evidence that this character could be sex linked. It is shown that the mutant can be infected by Schizotrypanum cruzi. The mutant strain is named "R. O. R".